Pengaruh Pendidikan Kewirausahaan Terhadap Kemampuan Merancang Strategi Bisnis Mahasiswa - Telaumbanua, Prety (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the extent to which entrepreneurship education in higher education contributes to students' ability to design effective business strategies. The research method used was quantitative descriptive with a survey approach. Data were collected from students who had taken entrepreneurship courses through a structured questionnaire. The results showed that entrepreneurship education significantly improved students' theoretical understanding and practical skills in conducting market analysis, financial planning, and risk mitigation. However, its effectiveness is highly dependent on the experiential learning method. These findings recommend the need for a curriculum that more integrates theory and practice of business simulations.